Exploring the Interplay Between Teacher Retention and Job Satisfaction - Siyamthanda Wendy Mvana (Social Sciences and Education Research Review)
This article explores the complex relationship between teacher retention and job satisfaction, drawing insights from Kalleberg's (1977) and Skaalvik and Skaalvik's (2017) models. It examines key factors influencing teacher satisfaction, including work values, job demands, psychological factors, supportive environments, and autonomy. Kalleberg's model emphasises the alignment of work values and job rewards, highlighting intrinsic rewards, convenience, financial stability, career advancement, and resource adequacy. Skaalvik and Skaalvik's model focuses on balancing job demands and resources to prevent burnout and enhance retention. Autonomy emerges as a crucial factor, empowering teachers through decision-making freedom and self-development opportunities. By understanding these elements, educational institutions can develop strategies to improve teacher retention, ultimately benefiting the educational system. The insights from these models provide valuable guidance for fostering a dynamic and effective educational environment.